PH-Controlled Synthesis of Electrolytic Manganese Dioxide Materials for Alkaline MnO2/Zn Batteries. (10th January 2017) - Nesvaderani, Farhang; Bonakdarpour, Arman; Wilkinson, David P
Abstract : A systematic study of the effect of electrolysis acid concentration on the physical and electrochemical properties of electrolytic manganese dioxide (EMD) was conducted. High acid concentrations (> 2 M H2 SO4 ), lead to multiphase production of manganese dioxide with poor electrochemical behavior; however, in low to mid-range acidic environments, superior EMD (compared to a commercial product) was obtained. With an electrolysis bath containing 1 M MnSO4 and 2 M H2 SO4, the EMD produced had approximately twice the surface area (86.4 m 2 gEMD -1 ) and structural water content (4.4 %) of that of a commercial sample. The aforementioned synthesized EMD furthermore had an improved energy efficiency and an average specific capacity of approximately 65 mAh gEMD -1 after 100 cycles showing about 25 mAh gEMD -1 higher capacity compared to the commercial sample.